The broader language phenotype of autism: a comparison with specific language impairment - Whitehouse, A; Barry, J; Bishop, D (Wiley, 2007)
Background: Some individuals with autism spectrum disorders (ASD) experience linguistic difficulties similar to those found in individuals with specific language impairment (SLI). Whether these behaviours are indicative of a common underlying genetic cause or a superficial similarity is unclear. Methods: Standardised language assessments were administered to three participant groups: parents of children with ASD (Par-A), parents of children with specific language/literacy impairment (Par-L) and parents of typically developing children (Par-T) (n=30, in each group). Additionally, the Autism-Spectrum Quotient (AQ) was used to assess autism-like tendencies, in particular, social language use. Results: The Par-A group performed better than the Par-L group (and identical to the Par-T group) on all language tests. Conversely, the Par-A group was characterised by higher levels of pragmatic difficulties than the other two groups, as measured by the communication subscale of the AQ. Conclusions: No evidence was found for a shared phenotype in parents in children with ASD and SLI. A model is presented describing the relation between SLI and ASD.